1992
DOI: 10.1164/ajrccm/145.4_pt_1.872
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic, Morphometric, and Biochemical Studies of the Premature Baboon with Bronchopulmonary Dysplasia

Abstract: Pathophysiologic, morphometric, and biochemical (surfactant and coagulation-fibrinolytic parameters) features were studied in premature baboons with and without bronchopulmonary dysplasia (BPD). A total of 22 baboons were delivered by hysterotomy at 75% of gestation and randomized into two groups. Group 1 (PRN) animals were ventilated with high-frequency oscillation for 48 to 72 h and then changed to positive-pressure ventilation (PPV) while maintained on clinically appropriate oxygen for the 21-day experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 8 publications
4
73
0
1
Order By: Relevance
“…125-day PRN (BPD animals): These were delivered at 125 days' gestation, given intratracheal beractant (Survanta; Ross Laboratories, Seattle, WA) (100 mg/kg), intravenous saline (vehicle control), and ventilated for 14 to 21 days to maintain Pa O 2 saturation of approximately 90%, as described (19,34).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…125-day PRN (BPD animals): These were delivered at 125 days' gestation, given intratracheal beractant (Survanta; Ross Laboratories, Seattle, WA) (100 mg/kg), intravenous saline (vehicle control), and ventilated for 14 to 21 days to maintain Pa O 2 saturation of approximately 90%, as described (19,34).…”
Section: Animalsmentioning
confidence: 99%
“…Paraformaldehyde-fixed tissues were processed into paraffin as described (34). Immunostaining was performed using our own rabbit anti-bombesin antisera (22) and monoclonal antibodies for SMA (1:100; Sigma) and CD31 (1:100; PharMingen, San Diego, CA) (35).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Although the use of milder ventilation strategies, exogenous surfactant, and antenatal steroids has reduced the incidence of airway inflammation and fibrosis, infants dying from BPD have simplified alveoli that are less vascularized (2). Likewise, alveolar simplification and disorganized vasculature is seen in preterm baboons (3,4) and in term rodents exposed to hyperoxia at birth (5,6). Oxidative stress caused by high oxygen exposure or by the inflammatory response to oxygen-induced cell injury promotes alveolar simplification by suppressing expression of angiogenic factors such as vascular endothelial cell growth factor (VEGF) (for review, see Ref.…”
mentioning
confidence: 99%
“…Surviving animals manifested histological evidence for alternating areas of atelectasis/emphysema, bronchiolar necrosis, early alveolar wall and peribronchial fibrosis, and squamous metaplasia of the airways, all classic findings of old BPD (19). deLemos and colleagues (20,24,28) further refined this model. They showed that a pro re nata (PRN) approach to oxygen therapy at 140 days of gestation (a relatively more mature preterm infant) allowed for complete recovery from HMD and was not accompanied by clinical, radiographic, and pathological manifestations of BPD.…”
Section: -Day Model ("Old Bpd")mentioning
confidence: 99%